Biotechnology : academic cell updates - Clark, David P.; Pazdernik, Nanette Jean (Academic Cell Press, 2012)
Approaches modern biotechnology from a molecular basis, which grew out of the increasing biochemical understanding of physiology. This text covers a wide realm of topics, including the forensics used in crime scene investigations, the burgeoning field of nanobiotechnology, bioethics and other topics in the world of biotechnology